Excitation wavelength dependent macromolecular super-strong cellulose-based intelligent packaging material and preparation method thereof

By incorporating small amounts of AAQ and DR chromophores into cellulose acetate, CA-AAQ and CA-DR films were prepared, solving the problem of insufficient barrier properties and mechanical strength of cellulose-based films under humid conditions, and realizing the application of high-strength and intelligent packaging materials to replace petroleum-based plastics.

CN120923871APending Publication Date: 2025-11-11HUAIYIN TEACHERS COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511057112.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-30
Publication Date
2025-11-11

AI Technical Summary

Technical Problem

Existing cellulose-based films have poor barrier properties and mechanical strength under humid conditions, and smart packaging materials are vulnerable to hacking threats, making them unable to effectively replace petroleum-based plastics.

Method used

By incorporating trace amounts of 1-aminoanthraquinone (AAQ) and Disperse Red 60 (DR) chromophores into cellulose acetate (CA), CA-AAQ and CA-DR films were prepared by solvent evaporation, establishing strong hydrogen bonds and electrostatic interactions, thereby improving mechanical strength and wavelength-dependent fluorescence response.

Benefits of technology

The prepared thin film has superior mechanical properties, good wavelength-dependent fluorescence response, and biodegradability, and can effectively replace petroleum-based plastics for application in OLEDs, smart electronics, and smart packaging materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120923871A_ABST
    Figure CN120923871A_ABST
Patent Text Reader

Abstract

The invention discloses an excitation wavelength dependent macromolecular super-strong cellulose-based intelligent packaging material and a preparation method thereof. The film material is prepared by doping less than 0.002% (w / w) of a chromophore into a biopolymer. The chromophore is 1-amino anthraquinone or disperse red 60. The biopolymer is at least one of cellulose acetate, starch, chitosan and polylactic acid. Dropwise adding the chromophore solution into the biopolymer solution, and stirring for 0.5-3 hours; and pouring the mixture into a glass plate, placing in a constant-temperature box, evaporating the solvent, and stripping to obtain the film. The excitation wavelength-dependent cellulose-based intelligent packaging film material is applied to manufacturing of OLED (Organic Light Emitting Diode), intelligent electronics and intelligent packaging materials as well as protection of ultraviolet rays and management of visible light.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of smart materials, specifically relating to a wavelength-dependent macromolecular ultra-strong cellulose-based smart packaging material and its preparation method. Background Technology

[0002] Wavelength-dependent smart materials have garnered significant attention in organic light-emitting diodes (OLEDs), other electronic materials, and smart packaging applications. However, these materials are widely made from petroleum-based plastics. Petroleum-based plastics are mass-produced globally due to their versatility, low cost, high barrier properties, and mechanical strength. Currently, approximately 400 million tons of plastic waste are generated annually, and this figure is increasing over time. The vast majority of plastic waste is released into the natural environment, causing severe pollution to aquatic, terrestrial, and marine life, with only 20% effectively managed. This increasing production not only leads to the depletion of non-renewable resources but also poses a worrying pollution threat to terrestrial and aquatic environments, shortening the lifespan of aquatic organisms. Furthermore, the impact of plastic-based materials on human health is intensifying daily due to the increasing presence of microplastics, flame retardants, plasticizers, and colorants in drinking water and the environment. The only way to control the production of plastic-based materials and manage global plastic pollution is to reduce their production, find sustainable alternatives, and control their release into the natural environment.

[0003] Due to global economic competition and increasing consumer demand for electronic devices, e-waste is being added to our environment at alarming rates, posing a serious environmental threat due to the toxicity and non-degradability of e-waste products. To address this e-waste challenge, more sustainable, renewable, biodegradable, and cost-effective raw materials such as cellulose can serve as effective alternatives to electronic applications and promote a circular economy. The development of environmentally friendly, sustainable, biodegradable smart materials from natural resources to replace plastic-based electronics and smart packaging materials is receiving significant attention.

[0004] However, their large-scale production remains negligible compared to synthetic plastics. Among natural polymers, cellulose, based on its abundant OH groups, significant biodegradability, light weight, non-toxicity, and abundant sources, has attracted particular attention for packaging applications. Researchers and scientists have been working to develop cellulose-based films with the impressive mechanical properties required by the smart packaging application market. For example, Droguet and colleagues... [1] Meter-scale cellulose nanocrystal films were fabricated using a solvent evaporation method. These biodegradable films, exhibiting good optical response, were then milled into pigments and glitter agents for photonics and smart packaging applications. Gan et al. [2]Wood-based films with a thickness of up to 10 μm were developed directly from natural wood for acoustic applications. These films exhibit a 20-fold increase in tensile strength and are used to manufacture wooden diaphragms for loudspeakers, microphones, and hearing aids, replacing non-degradable plastic-based products. Furthermore, cellulose-based room-temperature phosphorescent cationic materials were reported by incorporating cyanomethylimidazolium cations and chloride anions into the cellulose chain. This study proposes that physical interactions such as hydrogen bonding and electrostatic attraction between the cations, anions, and residual OH groups in cellulose play a crucial role in suppressing non-radiative transitions in room-temperature phosphorescent materials. These materials, dissolved in water, can be formulated into phosphorescent films and paper for smart packaging and anti-counterfeiting applications. [3-5] .

[0005] To date, films developed from sustainable materials such as cellulose still face two major problems. First, due to their low porosity and poor hydrophilicity, films exhibit poor barrier properties and mechanical strength under humid conditions. Second, thanks to advancements in information science and artificial intelligence (AI), packaging materials with software-generated labels and barcodes are undoubtedly vulnerable to hacking.

[0006] References:

[0007] [1]BEDroguet,H.-L.Liang,B.Frka-Petesic,RMParker,MFLDe Volder,JJBaumberg,S.Vignolini,Nat.Mater.2022,21,352.

[0008] [2]W.Gan,C.Chen,H.-T.Kim,Z.Lin,J.Dai,Z.Dong,Z.Zhou,W.Ping,S.He,S.Xiao,M.Yu,L.Hu,Nat.Commun.2019,10,5084.

[0009] [3]X.Zhang,Y.Cheng,J.You,J.Zhang,C.Yin,J.Zhang,Nat.Commun.2022,13,1117.

[0010] [4]LPManker,GRDick,A.Demongeot,MAHedou,C.Rayroud,T.Rambert,MJJones,I.Sulaeva,M.Vieli,Y.Leterrier,A.Potthast,F.Maréchal,V.Michaud,H.-A.Klok,JSLuterbacher,Nat.Chem.2022,14,976.

[0011] [5]Q.Gao,M.Shi,Z.Lü,Q.Zhao,G.Chen,J.Bian,H.Qi,J.Ren,B.Lü,F.Peng,Adv.Mater.2023,35,2305126. Summary of the Invention

[0012] To address the aforementioned issues, this invention designs and prepares wavelength-dependent cellulose-based smart packaging films CA-AAQ and CA-DR. These materials possess excellent flexibility, superior strength, and heat-sealing properties, making them suitable as alternatives to plastics.

[0013] We constructed large-scale, scalable, ultra-strong, and intelligent thin films by incorporating trace amounts of two chromophores, less than 0.002% (w / w), such as 1-aminoanthraquinone (AAQ) and Disperse Red 60 (DR), into DMF via a simple solvent evaporation method. The system thin film fabrication scheme is as follows: Figure 1 As shown in Figure A, the prepared films exhibit superior mechanical strength. Film strips with a thickness of 0.19-0.27 mm and a width and length (1 cm × 7 cm) can withstand a weight of 5 kg without deformation. Both CA-AAQ and CA-DR films provide excellent wavelength-dependent fluorescence responses, stemming from the film's chromophores and randomly generated copolymer structure, as well as the ESIPT (Excited-State Intramolecular Proton Transfer) phenomenon, which depends on the excitation light energy, thus altering the fluorescence color at different excitation wavelengths. The CA-AAQ film displays a deep yellow at 254 nm excitation, a pinkish-red at 300 nm excitation, and a purple at 365 nm excitation. The CA-DR film displays a brick-red at 254 nm excitation, a pale pink at 300 nm excitation, and a purple at 365 nm excitation, indicating significant potential for smart packaging applications. These films exhibit superior characteristics by constructing CA nanosheets that slide randomly, with AAQ and DR molecules incorporated into the CA sheets. Strong hydrogen bonds and electrostatic attraction are established between the freely floating cellulose acetate nanosheets. The freely floating cellulose acetate nanosheets contain multiple -COCH3 and -OH groups dissolved in DMF, while AAQ and DR possess -NH2 and -C=O groups. Figure 1 B). This work is expected to provide new insights into the industrial-scale production of cellulose-based super-strong and smart materials for sustainable applications such as OLEDs, smart electronics, and smart packaging materials, in order to replace traditional plastic-based materials in the future.

[0014] A wavelength-dependent cellulose-based smart packaging film material is prepared by incorporating less than 0.002% (w / w) of chromophores into a biopolymer.

[0015] The chromophore is 1-aminoanthraquinone or Disperse Red 60.

[0016] The biopolymer is at least one of cellulose acetate, starch, chitosan, and polylactic acid.

[0017] The chromophore is dissolved in DMF at a concentration of 0.1-2 mg / mL, preferably 0.5 mg / mL.

[0018] The amount of chromophore incorporated into the biopolymer is: 0.0001 mg to 0.0005 mg of chromophore incorporated into each gram of biopolymer.

[0019] Preferably, both chromophores were dissolved in DMF at similar concentrations (0.5 mg / mL). Then, AAQ / DMF solution (2 mL, 3 mL, 4 mL, and 5 mL, respectively (1 mg, 1.5 mg, 2 mg, and 2.5 mg, ranging from 1 mg to 2.5 mg)) and DR / DMF solution (1 mL, 2 mL, 3 mL, and 4 mL, respectively (0.5 mg, 1 mg, 1.5 mg, and 2 mg, ranging from 0.5 mg to 2 mg)) were added to each flask containing 5 g of dissolved cellulose acetate. Because the DR / DMF solution is darker in color, a smaller amount of DR / DMF solution was used to reduce film color.

[0020] The preparation method of the wavelength-dependent cellulose-based smart packaging film material includes the following steps:

[0021] S1. Dissolve the biopolymer in a solvent and stir for 1–3 hours;

[0022] S2. At 50–80°C, add the chromophore solution dropwise to the biopolymer solution and stir for 0.5–3 hours.

[0023] S3. Pour the mixture into a glass plate, place it in a constant temperature oven, evaporate the solvent, and peel off to obtain a film.

[0024] The concentration of the biopolymer solution is 0.05 g / mL to 1 g / mL.

[0025] The concentration of the chromophore is 0.1 mg / mL to 2 mg / mL.

[0026] Applications of the excitation wavelength-dependent cellulose-based smart packaging film material in the manufacture of OLEDs, smart electronics, and smart packaging materials.

[0027] Applications of the excitation wavelength-dependent cellulose-based smart packaging film material in protecting against ultraviolet light and managing visible light.

[0028] Beneficial effects:

[0029] The synthesis and characterization of CA-AAQ and CA-DR smart films were conducted using a simple method to prepare smart films by incorporating small amounts of AAQ and DR into CA dissolved in DMF. The incorporation of small amounts of AAQ and DR into CA plays a crucial role in enhancing its mechanical strength. Both prepared films exhibited reliable excitation wavelength dependence, fluorescence, biodegradability, and scalability. This research opens new avenues and offers an important solution to addressing the world's leading plastic pollution problem by replacing synthetic plastic materials with bio-based plastics. Attached Figure Description

[0030] Figure 1 A) A scheme demonstrating a method for manufacturing ultra-intelligent thin films. B) A proposed interaction mechanism between CA nanolayer chains and the doped AAQ / DR dissolved in DMF before and after stretching.

[0031] Figure 2 A) Transparency of CA-AAQ films by increasing AAQ concentrations by 1 mg, 1.5 mg, and 2 mg in 5 g CA, respectively; (i) Transparency on paper; (ii) Transparency on a tree; (iii) Transparency after stretching; B) Comparison of CA-DR films before and after stretching under similar conditions; C, D) Large-scale preparation of CA-AAQ and CA-DR films for smart packaging applications; E, F) Characterization of CA-AAQ and CA-DR films by FTIR; G, H) UV and visible light blocking properties of CA-AAQ and CA-DR films. I) XRD spectra of CA and CA-AAQ films.

[0032] Figure 3 A, B) CA-AAQ and CA-DR film strips of width and length (1cm × 7cm) bearing different weights (500g, 1kg, 2kg, and 5kg); C, D) CA-AAQ and CA-DR films exhibiting various mechanical tensile images; E) Tensile strain and tensile stress properties of four different CA-AAQ-based films F-1, F-2, F-3, and F-4 as AAQ concentration increases (1mg, 1.5mg, 2.0mg, and 2.5mg); F) Tensile strain and tensile stress properties of four different CA-DR-based films F-1, F-2, F-3, and F-4, showing the changes in strength and binding energy of CA and CA-AAQ films as DR.G and H) Cls concentrations increase (0.5mg, 1.0mg, 1.5mg, and 2.0mg).

[0033] Figure 4A) Comparison of SEM images of CA film (A) and CA-AAQ film before and after stretching (b, c); Magnified SEM image of CA-AAQ film (surface side) showing random CA nanosheets sliding on one side of the other (d, e, f); Magnified SEM image of CA-AAQ stretched film (cross-section of the fracture side) showing random CA nanosheets sliding on one side of the other (g, h, i); B) Comparison of SEM images of CA film (a) and CA-DR film before and after stretching (B, c); Magnified SEM image of CA-DR film (surface side) showing random CA nanosheets sliding on one side of the other (d, e, f); Magnified SEM image of CA-DR stretched film (cross-section of the smooth cut side) showing CA nanosheets sliding on one side of the other (g, h, i).

[0034] Figure 5 A) Fluorescence images of four different shapes of CA-AAQ films under visible light (top) and ultraviolet light at 254nm, 300nm, and 365nm (bottom). B) Heat sealing of packaging film bags using a laminator (a) CAAAQ-based packaging film shopper containing tomatoes for real-time smart packaging applications (b) Fluorescence images of the packaged shopper under ultraviolet light at 254nm, 300nm, and 365nm (c) C) Four different shapes of CA-DR films under visible light (top) and ultraviolet light at 254nm, 300nm, and 365nm (bottom); D) Heat sealing of packaging film shopper using a laminator (a) CADR-based packaging film shopper containing peanuts for real-time smart packaging applications (b) Fluorescence images of the packaged shopper under ultraviolet light at 254nm, 300nm, and 365nm (c).

[0035] Figure 6 A, C) FTIR spectra of CA-AAQ and CA-DR films before and after 180 days of aging. B, D) UV-Vis spectra of CA-AAQ and CA-DR films before and after 180 days of aging. E) SEM images of CA-AAQ (top) and CA-DR (bottom) films after 180 days of aging.

[0036] Figure 7 A) Large-scale applications of CA-AQ and CA-DR films for light management in large buildings and automobiles. B) Comparison of biodegradation and environmental pollution between plastic-based and cellulose-based materials;

[0037] Figure 8 Tensile strain of CA-AAQ films with different AAQ concentrations.

[0038] Figure 9 Waterproof performance of CA-AAQ film.

[0039] Figure 10 Waterproof performance of CA-DR film.

[0040] Figure 11 Smooth cut surfaces and fracture surfaces of CA-AAQ and CA-DR films.

[0041] Figure 12 High-temperature stability of CA-AAQ thin film.

[0042] Figure 13 High-temperature stability of CA-DR thin films.

[0043] Figure 14 Degradation properties of CA-AAQ and CA-DR films. Detailed Implementation

[0044] The chemicals and materials used in the experiment, such as analytical grade 1-aminoanthraquinone (AAQ), Disperse Red 60 (DR), cellulose acetate (CA), and N,N-dimethylformamide (DMF), were purchased from Shanghai Maclean Biochemical Co., Ltd., and anhydrous ethanol (95%) was purchased from Sigma-Aldrich.

[0045] Example 1

[0046] Preparation of ultra-strong fluorescent films: Ultra-strong transparent fluorescent films were prepared using the following simple method:

[0047] In an oil bath at 50°C, 5g of cellulose acetate was dissolved in 70mL of DMF in a 250mL Erlenmeyer flask and stirred for 2 hours (to prepare 8 samples).

[0048] Dissolve AAQ in DMF by increasing the volume (2 mL, 3 mL, 4 mL, and 5 mL).

[0049] 0.5 mg / mL, and 1 mg, 1.5 mg, 2 mg, and 2.5 mg, with values ​​ranging from 1 mg to 2.5 mg.

[0050] mg) was added dropwise to each of the dissolved cellulose acetate flasks, and the mixture was stirred at 60°C for 1 hour;

[0051] Dissolve DR in DMF at a concentration of 0.5 mg / mL (1 mL, 2 mL, 3 mL, and 4 mL).

[0052] (The amounts of 0.5 mg, 1 mg, 1.5 mg and 2 mg, respectively, ranging from 0.5 mg to 2 mg) were added dropwise to each of the dissolved cellulose acetate flasks, and the mixture was stirred at 60°C for 1 hour.

[0053] In this example, 5 grams of cellulose acetate were added, with AAQ ranging from 1 mg to 2.5 mg and DR ranging from 0.5 mg to 2 mg.

[0054] Finally, the mixture was poured into a 20cm × 20cm glass petri dish and kept in a 60°C oven for 2 hours. After DMF evaporation, the ultra-highly transparent fluorescent films were easily peeled off from the glass petri dish. They were named CA-AAQ-film-1, CA-AAQ-firm-2, CA-AAK-film-3, and CA-AAQ-film-4, and CA-DR-F1, CA-DR-F2, CA-DRF3, and CA-DR-F4, respectively, and used for further research.

[0055] Example 2

[0056] In an oil bath at 50°C, 12 g of cellulose acetate dissolved in 130 mL of DMF was used (then 8 mL of AAQ and 6 mL of DR (dissolved in DMF, 0.5 mg / mL) were added, and the solution was cast into a large 30 cm × 30 cm glass petri dish to develop large scalable films.

[0057] Characterization: Performed on a Nicolet iN10MXDA (Thermo Fisher Scientific) equipped with attenuated total internal reflection (ATR).

[0058] Fourier transform infrared spectroscopy was performed. Thirty-two scans were conducted, scanning the sample in the range of 650 cm⁻¹ to 4000 cm⁻¹, with a resolution of 4 cm⁻¹. Fluorescence measurements were performed on a Hitachi F-4500 fluorescence spectrometer with an exit slit of 10 nm, a voltage of 700 V, and an excitation wavelength of 254 nm.

[0059] 300nm and 320nm. On an Autograph AGS-X (Shimadzu, Japan) universal testing machine at 10...

[0060] The mechanical properties of the film (1cm × 5cm) were tested at a rate of mm.min⁻¹. Mechanical measurements were performed at ambient temperature. The water contact angle was measured using a (SL200KS, KINO) contact angle meter. Each sample was tested three times, and the average value was calculated. The thermal stability of the film was checked on a Q500 instrument, heated from 30-650℃ at a rate of 10℃ / min under nitrogen atmosphere. Measurements were performed according to Chinese National Standard (YBB).

[0061] According to the instructions in 00082003-2015, under conditions of 25℃ and 50% humidity, use (12cm×12cm)

[0062] Oxygen permeability (cm³ / m²·24h·0.1MPa) of CA-AAQ and CA-DR films was examined using a gas transport analyzer (Labthink C101B). The test was conducted under a controlled atmosphere (temperature = 38°C, relative humidity = 0.1MPa).

[0063] Water vapor permeability tests were performed on a Labthink W3-031 instrument using (8cm × 8cm) CA-AAQ and CA-DR films at 90% (presumably referring to a specific pressure or metric). Thermo Scientific K-Alpha XPS was used.

[0064] The instrument was used for XPS analysis at a chamber pressure of 2.0 × 10⁻⁷ mbar, a filament current of 6 mA, and an operating voltage of 12 kV. References were used [G. Zhou, H. Zhang, Z. Su, X. Zhang, H. Zhou, L. Yu, C. Chen, X. Wang, Adv. Mater. 2023, 35, 2301398. C. Cai, F. Chen, Z. Wei, C. Ding, Y. Chen, Y.].

[0065] Wang, Y. Fu, Chem. Eng. J. 2023, 476, 146668. K. Zhu, H. Tu, P. Yang, C. Qiu, D. Zhang, A. Lu, L. Luo, F. Chen, X. Liu, L. Chen, Q. Fu, L. Zhang, Chem. Mater. 2019, 31, 2078]

[0066] The method reported in the paper was used to test biodegradability. After a specific time interval, the prepared CA-

[0067] AAQ and CA-DR films, as well as commercial polyethylene films, were buried in soil to assess degradation parameters.

[0068] The synthesis and characterization of CA-AAQ and CA-DR smart films were carried out using a simple method to prepare smart films by incorporating small amounts of AAQ and DR into CA dissolved in DMF. The incorporation of small amounts of AAQ and DR into CA plays a crucial role in enhancing its mechanical strength because the CA nanosheets slide randomly between each other, forming a complex hydrogen bond network between AAQ and DR molecules. This sliding phenomenon, where CA nanosheets bind to AAQ and DR molecules and establish complex hydrogen bonds and electrostatic interactions, endows the films with superior strength. The proposed interaction mechanism between -COCH3 and the C=O groups of CA and NH2, as well as the C=O groups of AAQ and DR, is as follows: Figure 1 As shown in B.

[0069] The developed films exhibited significant transparency. At extremely low concentrations of AAQ and DR (1 mg in 5 g CA), the transparency was maintained. However, increasing the concentrations of AAQ and DR slightly affected the transparency, but objects remained visible and readable. On the other hand, the super-strength was improved. When the films were stretched, the CA-AAQ and CA-DR films exhibited very high transparency compared to before stretching. Figure 2 (i), (ii), and (1, 2, top). However, after stretching the CA-AAQ film (iii) and the CA-DR film (3), the transparency completely disappeared, showing a color whitening phenomenon similar to that observed in various polymers. Figure 2 A, 2B). These results are further supported by SEM experiments, which explored the surface morphology of stretched and unstretched films. The stretched films showed that CA nanosheets randomly intercalated to each other by establishing strong hydrogen bonds between the CA layers and the embedded AAQ and DR chromophores, similar to the intercalation or sliding of CNF fibers, resulting in ultra-high strength. Furthermore, based on the significant transparency and ultra-high strength, we fabricated large-scale films by adding small proportions of AAQ and DR to a CA / DMF solution. Long-width (30cm × 30cm) films were fabricated for large-scale production and real-time applications in the smart packaging industry. Figure 2 (C, 2D). The prepared smart films were characterized and verified using various instrumental techniques. First, FTIR studies revealed the chemical composition and functional groups present in the prepared CA-AAQ and CA-DR smart films. Therefore, Fourier transform infrared spectroscopy was performed. The CA-AAQ film showed that CA exhibited a significant -CH stretching peak at 2895 cm⁻¹ and a significant C=O stretching peak at 1657 cm⁻¹.

[0070] After film preparation, the NH2 stretching peak of AAQ disappeared, indicating that the NH2 group established strong hydrogen bonds and / or electrostatic interactions with the OH and C=O groups of CA. Due to this interaction, the CH stretching peak of CA also shifted to 2907 cm⁻¹ and 2839 cm⁻¹ in CA-AAQ. Figure 2E). Furthermore, a new absorption peak appeared at 1732 cm⁻¹ for the C=O group. Other peaks representing the CA-AAQ peak shift were CH, CO, and NH. Similarly, FTIR studies were performed to test the CA-DR film. The results showed that CA exhibited a significant CH stretching peak at 2915 cm⁻¹ and a significant C=O stretching peak at 1674 cm⁻¹. In contrast, DR showed two NH₂ stretching peaks at 3445 cm⁻¹ and 3294 cm⁻¹, and a prominent C=O peak at 1581 cm⁻¹. However, after film fabrication, the NH₂ stretching peak of DR disappeared, indicating that NH₂ was bonded to the OH and C=O groups of CA through strong hydrogen bonds and / or electrostatic interactions to form the CA-DR film. Figure 2 Furthermore, C=O showed a peak shift from 1674 cm⁻¹ in CA to 1662 cm⁻¹ in the CA-DR film, while a new absorption peak appeared at 1731 cm⁻¹. In summary, these results clearly demonstrate that the chromophores AAQ and DR were successfully incorporated into the CA nanosheets, establishing a strong interaction and resulting in a super-strong, transparent, and intelligent film. Based on the aromatic AAQ and DR structures, the prepared CA-AAQ and CA-DR films also exhibited ultraviolet shielding properties. The films can also protect against visible light, suggesting their potential applications in various fields such as construction, automotive, and home, where they can not only protect against ultraviolet light but also manage visible light (…). Figure 2 G). Although CA films can block about 60% of ultraviolet radiation in incident sunlight, after incorporating AAQ into CA, CA-AAQ films can not only protect against up to 85% of ultraviolet radiation, but also effectively prevent about 85% of visible light (wavelength range 420 nm to 550 nm) from penetrating the film. To further verify the presence of various constituent elements in the CA-AAQ film, energy-dispersive X-ray analysis was performed. The results showed that due to the use of a large amount of CA compared to AAQ, the carbon content was about 86.48%, the oxygen content was about 11.63%, and the nitrogen content was 1.89%; due to the use of a very small amount of nitrogen-containing chromophores (<0.002%), the nitrogen content was very low compared to oxygen and carbon. These results clearly support the incorporation of AAQ into CA-AAQ films, which have nitrogen and oxygen atoms in their structure. Similarly, CA-DR films also have ultraviolet shielding properties. These films are able to shield and manage visible light (wavelength range 466 nm to 594 nm). Figure 2 H). The CA-DR film not only protects against up to 85% of ultraviolet radiation, but also effectively prevents approximately 85% of visible light (wavelength range of 466nm to 594nm) from penetrating through the film.

[0071] These findings indicate that very small amounts of AAQ and DR are effectively incorporated into CA nanosheets, which slide randomly against each other, establishing a vast intralayer and interlayer hydrogen bond network, thus providing additional strength to the prepared film. This suggests that such fabricated smart films can be effectively used not only in the OLED, electronic materials, and smart packaging industries, but also in the construction, automotive, and home industries for protection against sunlight. To further verify the presence of various constituent elements of DR in the prepared film, energy-dispersive X-ray analysis was performed, clearly showing a carbon content of approximately 86.47%, an oxygen content of approximately 13.49%, and a nitrogen content of 0.04%. These results further support the incorporation of DR into CA-DR films, which have nitrogen and oxygen atoms in their structure. Similarly, by examining the atomic number of CA in the CA-AAQ film, XRD revealed the crystallinity, crystal structure, and orientation of the CA fibers in the film. This understanding is crucial for predicting mechanical and barrier properties. Therefore, XRD studies were conducted on CA films and CA-AAQ films. Figure 2 I). The results show that the CA-AAQ film exhibits crystalline peaks at 18.2°, 24.5°, and 38.8°, which are almost identical to the crystalline peaks of the CA film at 18.3°, 24.7°, and 40.5°. These findings indicate that the CA-AAQ film retains the original peaks and crystallinity of the CA structure. Similar XRD results were observed by examining the CA-DR film, which also exhibits crystalline peaks at 18.5°, 24.8°, and 39.8°, almost identical to the crystalline peaks of the CA film at 18.4°, 24.7°, and 40.2°. These findings also indicate that the CA-DR film retains the original peaks and crystallinity of the CA structure.

[0072] 2.2. Mechanical properties of CA-AAQ and CA-DR films

[0073] In the large-scale fabrication of cellulose-based films, their thermal and mechanical properties are crucial characteristics for practical applications. The film's superior strength depends on its crystallinity, thickness, fiber strength, and porosity; films with higher crystallinity and thickness exhibit better weight barrier properties. Furthermore, film processing methods such as solvent casting and mechanical pressing also affect these properties. Therefore, these properties must be carefully investigated before large-scale production. However, we have introduced a new technique and a simple, scalable method to fabricate large, scalable, ultra-strong, and intelligent films, demonstrating excellent weight barrier properties for packaging applications. Film strips of varying widths and lengths (1cm × 7cm) can easily withstand different weights of 0.5kg, 1.0kg, 2.0kg, and even 5.0kg without deformation. Figure 3(A, 3B). The superior strength of this film strip means that CA-AAQ and CA-DR films can be used for large-scale production of plastic alternatives. Furthermore, mechanical properties are crucial for the practical usability of these ultra-strong films. The tensile properties of the film are improved if the cellulose fibers are arranged in a specific pattern and have higher crystallinity; conversely, the tensile properties decrease if the film contains voids and cracks. Therefore, tensile stress and tensile strain measurements were performed on CA-AAQ and CA-DR films, and the mechanical tensile images are shown below. Figure 3 As shown in C and 3D. The results show that the CA-AAQ film (1cm × 5cm) has a tensile strength as high as 510%, indicating its great practicality in market applications. Similarly, the CA-DR film (1cm × 5cm) shows even better results, with a maximum tensile strength of 553%. In addition, four CAAAQ-based films with thicknesses ranging from 0.19mm to 0.26mm were tested, but the AAQ concentration continued to increase (1.0mg, 1.5mg, 2.0mg, and 2.5mg). The tensile test results are as follows. Figure 3 As shown in Figure E, the results indicate that by adding less than 0.002% AAQ to CA, the tensile stress of the film remains almost unchanged, but the tensile strain of films 1, 2, 3, and 4 increases sharply to 410%, 460%, 490%, and 510%, respectively. Figure 8 Furthermore, compared to CA films, the prepared films exhibit strain deformation. The CA-AAQ films, their measurement specifications, and the percentage increase in tensile strain are shown in Table 1.

[0074] Table 1. Length and increase in tensile strain (%) of CA and CA-AAQ films before and after tensile testing

[0075]

[0076]

[0077] Similarly, tensile stress and tensile strain measurements were performed on the CA-DR film. Figure 3 F). Four films with nearly similar thicknesses, ranging from 0.19 mm to 0.27 mm, were tested, but with increasing DR concentrations (0.5 mg, 1.0 mg, 1.5 mg, and 2.0 mg). CA-DR films and their measurement results are shown in Table 2.

[0078] Table 2. Length and increase in tensile strain (%) of CA and CA-DR films before and after tensile testing

[0079]

[0080] The results showed that by adding DR at a concentration of less than 0.002% to CA, the tensile stress of the film remained almost unchanged, but the tensile strain of films-1,-2,-3, and-4 increased sharply to 340%, 425%, 502%, and 553%, respectively, with a linear change in tensile strain observed. However, strain deformation was observed compared to the CA film. This enhanced strength can be attributed to the development of numerous CA nanosheets that randomly slide against each other, establishing strong hydrogen bonds and electrostatic interactions between nanosheets with C=O and OH groups and with AAQ and DR molecules with C=O and NH2 groups. These findings demonstrate that AAQ and DR are effectively integrated into the CA chain, endowing them with exceptional strength through the establishment of strong hydrogen bonds and / or electrostatic attraction.

[0081] Similarly, X-ray photoelectron spectroscopy (XPS) is an important technique for studying the elements, composition, and chemical bonds on a sample surface by irradiating it with X-rays and measuring the kinetic energy emitted from the sample surface. Therefore, XPS studies were conducted to verify the interaction mechanism between the C=O,OH groups of CA and the C=O,NH2 groups of AAQ. C1s scanning spectra of CA and CA-AAQ films showed distinct C1s and O1s binding energy peaks at 284 eV and 532 eV, respectively. In addition to the C1s and O1 peaks, CA-AAQ and CA-DR films also showed an additional N1s binding energy peak at 400 eV, further confirming the successful incorporation of CA by AAQ and DR. Likewise, the CA film showed a C1s peak, which further split into three peaks: -C=C- at (284.2 eV), -C=O at (285.1 eV), and -C=O at (286.1 eV). However, after AAQ was incorporated into CA, the C1s peak in the CA-AAQ film showed significant changes in photoelectron intensity and binding energy. The C=C peak in the CA-AAQ film was observed at (284.3 eV), -CC at (286.2 eV), and -C=O at (288.5 eV), indicating their interaction in the CA-AAQ film. Figure 3G, 3H). More interestingly, the N1s scans (scans A to E) of the CA-AQ film are very different from those of the CA film. The binding energies of the CA films in the N1s scans (A to E) are observed at 407 eV, 403.8 eV, 399.3 eV, 396.7 eV, and 394.4 eV, respectively, which are significantly different from the binding energies of the CA-AAQ films in the N1s scans (A to E) at 407.3 eV, 404.3 eV, 399.1 eV, 396.3 eV, and 394.4 eV. The CA-AAQ films also show a significant change in the photoelectron intensity of the N1s scan. These findings suggest that the -NH2 group of AAQ is clearly hydrogen-bonded to and / or exhibits electrostatic interaction with the COCH3 group of CA, and no peaks are shown in the prepared films as indicated by the FTIR studies. Figure 2 XPS studies were also conducted to verify the interaction mechanism between the C=O and OH groups of CA and the C=O and NH2 groups of DR. The CA film showed a C1s peak that unconvoluted into three peaks at (284.3 eV): C=C, CC at (285.2 eV), and C=O at (286.1 eV). However, after DR was incorporated into CA, the C1s peak in the CA-DR film showed significant changes in photoelectron intensity and binding energy. The C=C peak of the CA-DR film was observed at (284.2 eV), CC at (285.5 eV), and C=O at (287.1 eV), indicating their interaction in the CA-DR film. More interestingly, the N1s scans of the CA-DR film (scans A to E) were very different from those of the CA film. N1s scans of the CA thin film showed binding energies of 407 eV, 403.8 eV, 399.3 eV, 396.7 eV, and 394.4 eV from scan A to scan E. In the CA-DR thin film, the binding energies changed significantly to 406.4 eV, 405.3 eV, 402.4 eV, 399.4 eV, and 395.3 eV, respectively, and the photoelectron intensity also changed substantially. Similarly, the CA thin film showed an O1s peak (C=O) at 531.6 eV, which was significantly increased in intensity in the CA-DR thin film. The CA-DR thin film also showed a CO peak at 532.9 eV, indicating that the active functional groups of CA and DR may interact.

[0082] For practical applications of bio-based plastic materials, water contact angle measurement is also an important parameter for evaluating the wettability of film surfaces and revealing their interaction with liquids, with potential applications in packaging, coatings, sensors, and microfluidic devices. Therefore, we tested the water resistance of CA-AAQ films. These films show that the addition of AAQ to CA significantly improves water resistance. Figure 9Typically, the water contact angle of CA films ranges from 60° to 70°. Adding 2 mL of AAQ solution (0.5 mg / mL dissolved in DMF) to a CA solution (5 g dissolved in 70 mL DMF) increased the water contact angle to 83°, and further increased it to 91° by increasing the AAQ concentration to 2.5 mg. Furthermore, the water contact angle of four CA-AAQ films was monitored every 30 seconds, with five points obtained for each of CA-AAK film-1, CA-AAQ-film-2, CA-AAK-film-3, and CA-AAQ-firm-4 within 150 seconds. A significant increase in the water contact angle of the CA-AAQ films was observed from 83° to 91°. However, CA-AAQ film-4, with the highest AAQ concentration, exhibited a more stable water contact angle relative to time (minimal variation from 91° to 89° within 150 seconds). The CA-AAQ film-4 exhibited greater stability over time, which can be attributed to the increased AAQ concentration. AAQ, being aromatic, enhances the hydrophobicity of the prepared film. Similarly, we tested the water contact angle of the CA-DR film. The results show that integrating DR into CA slightly improves the film's water resistance. Figure 10 By adding 2 mL of DR solution (0.5 mg / mL dissolved in DMF) to a CA solution (5 g dissolved in 70 mL DMF), the water contact angle increased to 95° and decreased to 73° over time. Furthermore, the water vapor transmission rate and oxygen transmission rate of the CA-AAQ and CA-DR based films were tested. The results showed that their water vapor transmission rates were 5.185 × 10⁻¹⁴ g·cm / cm²·s·Pa and 4.679 × 10⁻¹⁴ g·cm / cm²·s·Pa, respectively, and their oxygen transmission rates were 50.95 cm³ / m²·24h·0.1 MPa and 10.01 cm³ / m²·24h·0.1 MPa, respectively.

[0083] However, thermogravimetric analysis (TGA) is an important analytical technique used to examine the thermal stability, decomposition temperature, and presence of volatile compounds in developing films. This information is indispensable for safe processing and packaging in the food industry because it has real-time application value. Based on these facts, we conducted TGA studies on CA-AAQ and CA-DR films to sense weight loss with temperature. The CA film and four CA-AAQ films revealed a two-stage thermal decomposition behavior, occurring around 290°C for the CA film, around 278°C for the CA-AAQ film, and around 465°C for both films. These degradation peaks are attributed to the thermal decomposition of the cellulose matrix and carbon combustion. The thermal decomposition behavior of the CA-AAQ film was slightly worse than that of the CA film. Similar experiments were conducted on the TGA studies of the CA and CA-DR films to sense weight loss relative to temperature. The CA film revealed a two-stage thermal decomposition behavior, occurring around 274°C due to water loss and around 454°C due to carbon combustion. These degradation peaks are attributed to the thermal decomposition of the cellulose matrix and carbon combustion. Furthermore, the thermal decomposition behavior of the CA-DR film is similar to that of the CA-AAQ film compared to the CA film. The first decomposition curve in the CA-DR film was observed at around 258 °C, followed by a second slow degradation carbon combustion peak at around 454 °C.

[0084] 2.3. SEM Study on the Ultra-Strength Mechanism The ultra-strength mechanism of the prepared thin film was realized through SEM study.

[0085] SEM studies revealed the surface morphology of the films, providing detailed images of pores, cracks, and fiber arrangements. SEM studies are crucial for understanding gas permeability, barrier properties, and film integrity. Therefore, CA-AAQ and CA-DR films were studied using SEM. Figure 4 As can be seen from the SEM images, the surface morphology of the CA-AAQ film did not undergo any significant changes compared to the CA film. Figure 4(A, a, b) Although both films exhibit smooth surfaces, the CA-AAQ film shows small dots on its surface, indicating that AAQ molecules are incorporated into the CA chains. However, when the CA-AAQ film is stretched, the surface morphology of the stretched film changes significantly, and a fibrous stretching pattern appears (c). By further magnifying the SEM images to 5 μm, 1 μm, and 500 nm, it can be clearly seen that the stretched film displays randomly oriented CA microlayers and nanolayers with sliding patterns that are bound to AAQ molecules through physical interactions, which provides excellent strength to the fabricated film (d, e, f). This random nanolayer sliding phenomenon is further confirmed by examining cross-sectional SEM images of the smooth cut side and the fractured side of the stretched film. Both films show similar results in terms of smooth cut side and fractured side images, therefore we ( Figure 4 Only one result is provided for each film. For the stretched CA-AAQ film, we show the cross-sections of the fracture side of the film at higher magnifications (e.g., 1 μm, 500 nm, and 200 nm). The results show the presence of numerous randomly oriented CA nanolayers, one sliding on top of the other, providing additional strength to the film doped with AQQ molecules (g, h, i). The smooth cut surface of the CA-AAQ film shows a SEM image similar to that of the CA-DR film. Figure 4 (Smooth cut side in B). In the CA-DR film, we show the cross-section of the smooth cut surface, and the results are as follows. Figure 4 As shown in Figure B, we present SEM images of the smooth-cut cross-section of the CA-DR film here, as the SEM images of the fractured side are very similar to those of the CA-AAQ film. In both films, the results indicate the formation of numerous randomly oriented CA nanolayers exhibiting a slip-through pattern, similar to the intercalation or slip-through pattern of CNF fibers. This results in strong intralayer and interlayer hydrogen bonds between the CA chains and the bound chromophores, conferring the film with exceptionally high strength. Figure 4 B, g, h, i). Smooth cut surfaces and fracture surfaces of CA-AAQ and CA-DR films, as shown in... Figure 11 As shown. However, no significant changes in membrane structure or membrane weight were observed after 10 days.

[0086] 2.4 Heat resistance properties of CA-AAQ and CA-DR films

[0087] For practical applications at different temperatures, the film should exhibit heat resistance. Therefore, CA-AAQ films were cut into widths and lengths (2cm × 4cm) and placed in a 40°C furnace for 1 hour. After a 1-hour interval, the temperature was increased by 10°C (e.g., 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, and 110°C) to examine the film's stability, color, or shape change behavior. However, even at temperatures as high as 110°C, the film exhibited high stability. By further increasing the temperature from 110°C to 120°C, the film changed from wheat-colored to chocolate-colored within 30 minutes. These results indicate that the CA-AAQ film is very stable, exhibiting very stable color and shape at the significantly high temperature of 110°C, and maintaining shape stability even at 120°C. Figure 12 Similar experiments were conducted using CA-DR films, which were cut into widths and lengths (2 cm × 4 cm) and placed in a furnace at 40°C for 1 hour. The temperature was increased by 10°C every hour (e.g., 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, and 110°C) to examine the film's color or shape change behavior. However, even at a high temperature of 120°C, the film exhibited high stability. These results indicate that the CA-DR film exhibits very stable color and shape at a significantly high temperature of 120°C and maintains its shape stability at high temperatures. Figure 13 ).

[0088] 2.5. Biodegradability, aging effects, and light management applications of CA-AAQ and CA-DR films

[0089] The biodegradability of cellulose-based films is one of their most attractive features, making them a promising alternative to traditional plastic films. Biodegradability is related to film thickness, crystallinity, and composting conditions such as humidity, temperature, microbial activity, and oxygen availability. All of these factors play a role in the decomposition process of cellulose-based films. Therefore, to explore the biodegradable properties, CA-AAQ films, CA-DR films, and commercially available polyethylene films were buried in soil to evaluate degradation parameters. On the one hand, visible light images after 0, 50, 100, and 180 days show that CA-AAQ and CA-DR films exhibit slight degradation due to the action of microorganisms in the natural environment. Biodegradability testing is still underway to examine the time required for complete degradation of the bio-based smart films. On the other hand, commercially available polyethylene films maintained their original shape even after 180 days. (See...) Figure 14 These results clearly demonstrate that the ultra-strong smart films prepared in our laboratory are ideal candidates for large-scale production of alternative plastic materials. Furthermore, the aging effects were evaluated using FTIR, UV-Vis, and SEM studies, with results as follows: Figure 6As shown in the FTIR results, the unaged CA-AAQ film exhibits a strong C=O absorption peak at 1674 cm⁻¹. After 180 days of aging, the intensity of the C=O peak at 1674 cm⁻¹ significantly decreased, indicating cellulose acetate degradation and deacetylation. The CH peak indicates a decrease in intensity and a slight wavelength shift after aging from 2916 cm⁻¹ to 2928 cm⁻¹. The intensity changes of other cellulose peaks at 1433, 1338, 1242, and 1092 cm⁻¹ clearly confirm the degradation of the CA-AAQ film after 180 days of aging. Figure 6 A). Similar FTIR results were observed in the CA-DR film after 180 days of aging, as shown in the following figures. Figure 6 As shown in Figure C. Following the FTIR results, UV-Vis results also confirmed the aging phenomenon. The unaged CA-AAQ film surface was smooth, exhibiting a strong absorption peak in the visible light region from 368 nm to 572 nm, with a transparency of approximately 80%. After aging, the film transparency decreased to 30%. Figure 6 B) Small bubbles appeared on the film surface, and the number of bubbles increased over time. On the other hand, the unaged CA-DR film showed a smooth surface and strong absorption peaks in the visible light region of 384 nm to 605 nm, indicating a transparency of approximately 75%. After aging, the film transparency decreased to 30%. These results indicate that changes in cellulose crystallinity and regeneration led to a rougher film surface. Furthermore, SEM studies further confirmed the aging phenomenon, as shown in the results... Figure 6 As shown in E. The surface of the unaged CA-AAQ film is smooth, without cracks or degradation. Figure 4 A), but after 180 days of aging, it became a rough surface with cracks and obvious degradation. Similar findings were observed in the aged CA-DR film. These findings further support our claim that the designed film is biodegradable and environmentally friendly.

[0090] The ultra-strong, intelligent, and large-scale scalable thin films prepared in our laboratory exhibit a high degree of excitation wavelength dependence, and have enormous potential applications in OLEDs, other flexible electronic materials, and smart packaging and security printing that can replace traditional plastics.

[0091] This study introduces an innovative technique to prepare a wavelength-dependent ultra-strong cellulose-based smart film using a simple solution casting method. In short, small amounts of AAQ and DR (<0.002% w / w) are incorporated into CA dissolved in DMF. The chromophores are integrated into the randomly oriented CA nanosheet structure, sliding against each other and forming intralayer and interlayer hydrogen bonds and / or electrostatic associations between the OH and C=O groups of the CA sheets. They also bind to the NH2 and C=O groups of AAQ and DR, endowing them with superior strength and heat-sealing properties. The prepared smart films, with thicknesses ranging from 0.19 mm to 0.27 mm and dimensions of 1 cm × 7 cm, can readily support weights of 0.5 kg, 1.0 kg, 2.0 kg, and even 5.0 kg without deformation. Furthermore, the water vapor transmission rates of the CA-AAQ and CA-DR films were 5.185 × 10⁻¹⁴ g·cm / cm²·s·Pa and 4.679 × 10⁻¹⁴ g·cm / cm²·s·Pa, respectively, and the oxygen transmission rates were 50.95 cm³ / m²·24h·0.1 MPa and 10.01 cm³ / m²·24h·0.1 MPa, respectively. Both films exhibited reliable excitation wavelength dependence, fluorescence, biodegradability, and scalability, which endows them with impressive potential for OLED, biodegradable electronics, and smart packaging applications. The prepared smart films showed excellent reproducibility across five batches, with similar findings, significant reliability, and significant biodegradability, as confirmed by water permeability tests, gas transport tests, and aging experiments. This research opens new horizons and provides an important solution to addressing the world's leading plastic pollution problem by replacing synthetic plastic materials with bio-based plastics.

Claims

1. A cellulose-based smart packaging film material with excitation wavelength dependent, characterized in that, The thin film material is prepared by incorporating less than 0.002% (w / w) of chromophores into a biopolymer.

2. The cellulose-based smart packaging film material with excitation wavelength dependence according to claim 1, characterized in that, The chromophore is 1-aminoanthraquinone or Disperse Red 60.

3. The cellulose-based smart packaging film material with excitation wavelength dependent according to claim 1, characterized in that, The biopolymer is at least one of cellulose acetate, starch, chitosan, and polylactic acid.

4. The cellulose-based smart packaging film material with excitation wavelength dependent according to claim 1, characterized in that, The chromophore is dissolved in DMF at a concentration of 0.1-2 mg / mL.

5. The cellulose-based smart packaging film material with excitation wavelength dependent according to claim 1, characterized in that, The amount of chromophore incorporated into the biopolymer is 0.0001 mg to 0.0005 mg per gram of biopolymer.

6. A method for preparing the wavelength-dependent cellulose-based smart packaging film material according to any one of claims 1 to 5, characterized in that, Includes the following steps: S1. Dissolve the biopolymer in a solvent and stir for 1-3 hours; S2. At 50~80℃, add the chromophore solution dropwise to the biopolymer solution and stir for 0.5~3h; S3. Pour the mixture into a glass plate, place it in a constant temperature oven, evaporate the solvent, and peel off to obtain a film.

7. The preparation method according to claim 6, characterized in that, The concentration of the biopolymer solution is 0.05 g / mL to 1 g / mL.

8. The preparation method according to claim 6, characterized in that, The concentration of the chromophore is 0.1 mg / mL to 2 mg / mL.

9. The application of the wavelength-dependent cellulose-based smart packaging film material of claim 1 in the manufacture of OLEDs, smart electronics and smart packaging materials.

10. The application of the wavelength-dependent cellulose-based smart packaging film material of claim 1 in protecting against ultraviolet light and managing visible light.